The Sufi Dimension in The Experience of The Artist Omar El Zahi Between Al-Hadra and Al-Shaabi Marriage - Mehdi BERRACHED (Turath)
The spiritual religious content formed an important criterion in the selection of artists of the "Châabi" song in the city of Algiers when choosing the sung repertoire « Melḥun », that has been dubbed "Al-Djid" in contrast to a repertoire with themes of love and wine, since this musical style was once called "Al-Madh". Therefore, weddings in the city of Algiers were filled with the poems of the Sufi poet Sidi Lakhdar Ben Khlouf, Mohammed Ben Msaib, and others from Algeria, and the poems of Abdul Aziz Al-Maghrawi, Sheikh Mohammed Al-Najjar, Al-Arabi Al-Miknassi, and others from Morocco.